2020
DOI: 10.3747/co.27.6533
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in a Real-World Study of Patients with Metastatic Colorectal Cancer Treated with Trifluridine/Tipiracil

Abstract: Background Quality of life (qol) is important for oncology patients, especially for those with late-stage disease. The present study was initiated to address the lack of published prospective data about the qol benefits of trifluri­dine/tipiracil (tfd/tpi) compared with best supportive care (bsc) in patients with refractory metastatic colorectal cancer (mcrc). Methods This prospective, cross-sectional, non-interventional study used multidimensional validated scales to evaluate patient-reported qol in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(40 reference statements)
2
3
0
Order By: Relevance
“…The number of returned/evaluable questionnaires decreased over time, which may limit further conclusions that can be drawn. Nevertheless, the results of patient‐reported QoL in our study are in line with data reported in several clinical trials, indicating a preservation of QoL in patients with mCRC treated with FTD/TPI 28‐30 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The number of returned/evaluable questionnaires decreased over time, which may limit further conclusions that can be drawn. Nevertheless, the results of patient‐reported QoL in our study are in line with data reported in several clinical trials, indicating a preservation of QoL in patients with mCRC treated with FTD/TPI 28‐30 …”
Section: Discussionsupporting
confidence: 91%
“…Evaluation of effectiveness of treatment in subgroups of patients with different characteristics might provide valuable information in terms of prognostic value. In TACTIC, PFS was comparable between the prognostic subgroups (BPC/GPC vs PPC), while OS was markedly longer in the subgroups of patients with BPC (median 13.3 months) or GPC (median 8.9 months) as compared to the subgroup of patients with PPC (median 5.1 months), which is in line with the data reported in the explorative post hoc analysis of the results of the RECOURSE trial ( [28][29][30] To potentially achieve full benefit of therapy, maintaining a high relative dose intensity is of key importance. The median relative dose intensity of FTD/TPI in TACTIC was 91.3%, which is in line with the 89% reported in the RECOURSE trial.…”
Section: Discussionsupporting
confidence: 87%
“…A Canadian non-interventional study assessed HRQoL in 50 FTD/TPI-treated patients and 55 patients receiving BSC. 16 Unlike the TALLISUR and PRECONNECT trial, QoL was assessed using the Rotterdam Symptom Checklist and the CRC-specific FACT Colorectal Cancer Symptom Index (FCSI). According to the former assessment, physical and psychological distress, activity level and overall global QoL were statistically significantly better in patients receiving FTD/TPI compared to patients receiving BSC.…”
Section: Discussionmentioning
confidence: 99%
“…Among 875 screened publications, 29 publications were selected, which reported on 26 studies: 5 RCTs, 7 , 8 , 12 , 26 30 11 non-RCTs, 31 41 and 10 prospective observational studies 15 , 42 50 ( Figure 1 ; Supplemental Table 3 ). Six studies involved FTD/TPI + BEV as an intervention.…”
Section: Resultsmentioning
confidence: 99%